Broiler Industry - Tellez-Isaias, Guillermo; Latorre, Juan D.; Martínez-Aguilar, Yordan (IntechOpen, 2022)
The poultry industry has been continuously evolving in multiple research and management areas, including hatchery practices, disease control, genetic selection, intestinal physiology, and nutrition, among others. For instance, it has been observed that amino acid requirements tend to change based on the different environmental and immunological challenges that an animal is undergoing. In addition, a continuous improvement in feed efficiency and growth performance has also affected meat quality parameters. Additionally, research on the impact of hatchery settings and environmental conditions on embryonic development and performance parameters is crucial for an economically feasible production, considering the importance of animal welfare as well. This book provides a compilation of recent scientific information on different pivotal areas of the broiler industry.